An Introduction to Sociology - Serge Denisoff ([Place of publication not identifed] : [publisher not identified], 1983)
Sociologists are strangers in a familiar land by their own choice. They attempt to step back and look at the world in which they live. By temporarily withdrawing they try to understand society. To do this they must take the trouble to look beyond their everyday experiences and cherished beliefs. Sociologists present their research in such a way that ideas that seem to be facts can be either proved or refuted. By standing on the rainy corner the disgruntled passenger may establish the routing schedules of the bus company. Sociologists try to establish the existence of patterns in social life but under more comfortable conditions. Both the sociologist and the soggy passenger are trying to discover what is real in the everyday world.
1. Strangers in a familiar land -- 2. The origins of sociology -- 3. Research Methods -- 4. Society -- 5. Culture -- 6. Socialization -- 7. The family -- 8. Religion -- 9. Political institution -- 10. Mass communications -- 11. Stratification systems and theories -- 12. Social status in America -- 13. Intergroup relations -- 14. Deviance -- 15. Collective behavior -- 16. Social movement -- 17. Social change -- 18. Population and demography .
Includes bibliographical references and index.
Keywords: SOCIOLOGY